(3GdEMUGA GdhUaj hfXGe (BSPSS /s - (3UHQj , YRGes ((3YeGf(B: s (3YGde GdcJH GdMOjK(B, s, 2006)
(3ebOeI dOQGSI GdEMUGA(B-(3ebGjjS GdfRYI GdeQcRjI(B-(3ebGjjS GdJTJJ(B-(3GdYRhe(B-(3GdJhRjY GdWHjYj fXQjI GdEMJeGdGJ(B-(3GdEQJHGW hGdEfMOGQ HGdSdGSd GdRefjI(B-(3GdCQbGe GdbjGSjI(B-(3GdEMUGAGJ GdMjhjIs
Keywords: (3GdEMUGA GdhUajs; (3GdHjGfGJ GdEMUGFjIs; (3GdJMdjd GdEMUGFjs